Effects of sintering temperature on thermal, mechanical and dielectric properties of SiC/Si3N4 nanoparticles-inserted kaolinite–mullite - See, Alex (2016)
Malaysian kaolinite production and exports have declined despite increasing global consumption of kaolinite material in paper and whiteware industries. New applications for Malaysian kaolinite are necessary to improve its competitiveness in the global environment. This research was designed to test the hypothesis that insertion of nanoparticles within a micron grain-size matrix will form a composite material with enhanced values in thermal, mechanical and electrical properties. The matrix chosen was a kaolinite-mullite matrix and the nanoparticles selected were β-Silicon Carbide (SiC) and amorphous Silicon Nitride (SN). Both Silicon Carbide-Mullite (SC-M) and Silicon Nitride-Mullite (SN-M) composite powders were prepared with a mixed solution followed by conventional sintering in an argon environment at 1000 °C, 1100 °C and 1200 °C temperatures. XRD data of the SC-M composites yielded kaolinite-mullite products with embedded SiC presence. The SN-M composites however, yield the presence of α- and β-Silicon Nitride phases as the amorphous nanoparticles were detected to be crystalline by the XRD data. Densities of the composites were lower than the true density of the mullite matrix as the composites weights were influenced by the bulk densities of the nanopowders. Thermal diffusivity of the SC-M and SN-M composites yielded lower values as compared to the thermal diffusivity of the Kaolinite matrix itself. The thermal diffusivity values of both SC-M and SN-M were dependent on the presence of mullite concentration within the matrix. Mechanical measurements of the SC-M and SN-M composites yielded significantly higher compressive strength as compared to those of the matrix samples. Kaolinite-mullite samples presented layered fractures under the compression test with a maximum value of 21.3 MPa. The 5% SC-M sample yielded compression strength of 54.2 MPa. SiC additions higher than 5% have lower, linear compression relation with a sharp break at maximum. SN-M composites exhibited typical ceramic compression strength at low weight additions; higher SN additions displayed a constant compression loading effect followed by ceramic loading behavior with 30% SN-M displaying ultimate compressive strength of 110 MPa. Dielectric permittivity of the kaolinite-mullite matrix samples has low relaxation behavior with εr‟ values marked at 9.3 to 19.3 units (at 1 MHz) for room temperature measurement. The insertion of SiC nanoparticles has elevated the real dielectric permittivity range from 5.7 units to 17.1 at 1 MHz. Insertion of the SN nanoparticles exhibited dielectric suppression as the relative dielectric permittivity values were lower than those of the matrix itself, from 4.1 to 12.2 units at 1 MHz. The insertion of nanoparticles within the kaolinite-mullite matrix is fruitful as different properties can be examined in detail. Both SiC and SN nanoparticles yielded different degrees of enhancements in thermal, mechanical and electrical properties. The nanoparticles insertions were beneficial to thermal and electrical insulating behavior as well as mechanical compression strength.